An overview of Ehlers Danlos syndrome and the link between postural orthostatic tachycardia syndrome and gastrointestinal symptoms with a focus on gastroparesis - Wu, William; Ho, Vincent (Frontiers in Neurology, 2024)
There has been an increasingly reported association between Ehlers-Danlos syndrome (EDS), postural orthostatic tachycardia syndrome (POTS) and gastrointestinal disorders. EDS is a hereditary connective tissue disorder which may manifest as a spectrum of symptoms stemming from collagen defects. The prevalence of EDS is estimated to affect 1 in 5000 individuals which underscores its clinical significance. Notably the hypermobile form (hEDS) accounts for the majority of cases. POTS is characterised by orthostatic intolerance with and increase in heart rate on standing in the absence of hypotension. This condition predominantly affects women between 15-45 years of age. Gastrointestinal symptoms in the form of reflux, bloating and abdominal pain significant impact this population. Gastroparesis is a chronic disorder involving symptoms of delayed gastric emptying and may be closely associated with hEDS and POTS, and may be underreported. Autonomic dysfunction associated with hEDS has been proposed as the likely mechanism underlying POTS and gastrointestinal dysfunction though a clear pathophysiological process has not been established.